The effect of alcohol intake on breastfeeding duration in Australian women - Giglia, Roslyn; Binns, Colin; Alfonso, H.; Scott, J.; Oddy, W. (Wiley-Blackwell, 2008)
Aim: This study investigated the relationships between alcohol consumption and breastfeeding initiation and duration. Methods: Design and Setting: A 12-month longitudinal study was conducted in two public hospitals in Perth, Australia between September 2002 and July 2003. Intervention: Participating mothers completed a self-administered baseline questionnaire. Follow-up telephone interviews were conducted at 4, 10, 16, 22, 32, 40 and 52 weeks. Main outcome measures: Association of the relationships between alcohol consumption and breastfeeding initiation and duration. Results: After 6 months of follow-up, women who consumed alcohol at levels of more than two standard drinks per day were almost twice as likely to discontinue breastfeeding than women who drank below these levels (HR 1.9, 95% CI 1.1, 3.0). Conclusion: Consuming alcohol in excess of two standard drinks per day during lactation was found to be independently associated with shorter breastfeeding duration, even after consideration of previously identified predictors of breastfeeding duration. Guidelines that provide direction on safe alcohol consumption for lactating mothers may help support extended breastfeeding duration.